A Comparative Study on Customer Experience and Social Media Marketing of Amazon and Flipkart (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Customer experience is the consequence of association between an association and a customer  amid the length of their relationship. This relationship is comprised of three sections: the client  venture, the brand contact focuses the client associates with, and the conditions the client encounters  amid their great client encounter implies that a person's understanding amid all purposes of  contact coordinates a person's desire.Social media marketing provides discovery of new content  and also builds the link with the customers. Many people use social media to search various  products and services to which social media marketing acts as an effective tool.This paper shows  the comparative trend in customer experience and social media marketing of Amazon and  Flipkart.
Keywords: Social Media Marketing; Consumer Experience